Biological and Health-promoting Activity of Vinification Byproducts Produced in Spanish Vineyards - Anter, J.; Demyda-Peyras, S.; del Pilar Delgado de la Torre, M.; Campos-Sanchez, J.; Luque de Castro, M.D.; Muñoz- Serrano, A.; Alonso-Moraga, Á. (South African Journal of Enology and Viticulture, 2016)
Several by-products are produced in the Spanish agricultural system. Among them, fresh and vinified grape skins represent an abundant source of phenols with a potential nutraceutical value. Fresh grape skin extracts (FGSE) and vinification of grape skin extracts (VGSE) obtained by a microwave-assisted method have been chemically and biologically characterised. Their role in the maintenance of genetic stability was stated by in vivo genotoxic and antigenotoxic evaluations (Drosophilla melanogaster wing spot test), as well as by their potential chemopreventive effect (in an HL60 in vitro model). Total phenolic, anthocyanin and resveratrol contents were chemically characterised in the two extracts, showing some qualitative differences. Both extracts and resveratrol were not mutagenic in the Drosophila somatic mutation and recombination tests, and exerted antigenotoxic activities against hydrogen peroxide. They also showed cytotoxic activity to HL60 leukaemia cells, with an IC50 of 4.5μL/mL, 4.6μL/mL and 98μM respectively and induced apoptotic internucleosomic fragmentation in the HL60 cell line.